Casais sem filhos: as repercussões individuais e na relação conjugal - Vailati, Nídia (2011)
Family and marriage have undergone many changes throughout history. The traditional family has given place to new family configurations present in today s society. This scenery and also the possibility of, in understanding the movement in the vital cycle of childless couples, identifying other challenges that are specific to the conjugality other than parentality, have circumscribed the object of this paper, namely: to understand the effects of the absence of children in the marriage relationship. The methodological approach adopted is qualitative and the methodological strategy used is the individual and married life story. In order to reach our objective, we have established a few categories for analysis, namely: 1. How the couple was formed; 2. The Consequences. Among all the members of the couples interviewed we have observed statements on the fact that not having any children has made them more egotist, individualist and less tolerant to child noises, beliefs about themselves that may well refer to traits already present in their personality. The fact of being childless also liberates them to develop their individuality further, they are freer to make their choices, and they have a larger autonomy to dedicate themselves to other life projects, such as career and relationship. The conjugal relationship has a functionality that is able to cope with situations as unemployment and change in field of work without jeopardizing the relationship. The couples interviewed present a level of ego differentiation that has enabled them to live their choices, conjugal or other, with a higher degree of clarity and freedom, without suffering the interference of their families of origin